A Comprehensive Approach to Oral Health and the Prevention of Dental Caries in Saudi Arabia: Collaborative Efforts in Public Health, Health Administration, Dentistry, and Epidemiology - Dhafer Amer Alshehri; Hamza Abdul Rahman Amir Al Sharif; Ahmed Mansor R. Hagawi; Manal Abdulaziz Asiri; Huda Abdulaziz Asiri; Ali Amer Alshehri; Ahmed Alasmari; Ali Mohammed Abdullah Al Ahmari; Jamal Abdulrahman Alamry; Ali Abdullah Alshehri; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Oral health is a fundamental aspect of general health and human functioning, several areas of life being impacted in terms of physical, psychological or social aspects. Dental caries has been ranked as one of the most predominant non-communicable diseases worldwide and one that affects all ages. There is the high prevalence of dental caries among the population in Saudi Arabia and according to the existing studies it is even higher among children and teenagers. Aim of work: To explore a comprehensive approach to addressing oral Health and the prevention of dental caries by examining collaborative efforts involving public health, health administration, dentistry, and epidemiology. Methods: We conducted a comprehensive search in the MEDLINE database’s electronic literature using the following search terms: Comprehensive Approach, Oral Health, Prevention, Dental Caries, Saudi Arabia, Collaborative Efforts, Public Health, Health Administration, Dentistry, and Epidemiology. The search was restricted to publications from 2016 to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion: Understanding and avoiding dental caries in Saudi Arabia calls for a holistic and interdisciplinary endeavor in public health, health administration, dentistry, and the epidemiological sciences. Through understanding and addressing social determinants of health, utilizing technological solutions, as well as establishing strong interdisciplinary collaboration, the country can enable the reduction of caries rates and enhance the overall population’s health. Thus, sustained efforts towards education, prevention, and policy changes will help sustain the improvements in the realization of a healthy smile for all the Saudi citizens.